Leadership talks : candid conversations with academic leaders - Fernandez, Frank; Coulson, Hilary L.; Zou, Yali (Emerald Publishing Limited, 2024)
Offering aspiring leaders a chance to learn from the experience of deans, vice presidents, and presidents who have served at different types of institutions around the country, Leadership Talks: Candid Conversations with Academic Leaders, presents a half dozen extended interviews with current and former administrators that cover their paths to leadership, how they navigate evolving challenges in higher education, and how they have learned from failure. These leaders come from diverse backgrounds and have worked at a mix of public and private institutions. Their campuses ranged from two-year, open access institutions to selective four-year research universities in six states across the U.S. As colleges and universities face intensifying challenges, Leadership Talks offers a new model of seven essential skills and qualities for 21st century academic leadership. Many campus leaders will need to navigate a looming enrolment cliff, campus protests, increasing public scrutiny, budget cuts, and new court decisions and state legislation curtailing efforts to increase diversity. Each chapter offers insights about how campus leaders have addressed those challenges in the past and hope for how campuses can thrive in the future. Presenting a diverse and inclusive overview of academic leadership, this timely work will be of use and interest to current, future, and aspiring leaders in higher education, along with higher education scholars and students.
Keywords: Educational leadership.; Education, Higher.; Education -- Leadership.; Educational administration and organization.; Educational strategies and policy.; elektronické knihy; electronic books